2021
DOI: 10.1155/2021/9977951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Coronal Sealing Materials in the Endodontically Treated Teeth: An In Vitro Study

Abstract: In vitro studies have shown that rapid penetration of bacteria in the entire root canal system may occur after endodontic treatment without a coronal seal. A proper restorative technique is necessary to ensure a coronal seal and protection of the residual dental structure. The aim of this in vitro study was to evaluate the coronal sealing ability of the most relevant clinical materials by means of dye penetration (neutral red dye, Sigma-Aldrich, Germany), through a light spectrometric device, and to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A total of seven in vitro studies 3,[11][12][13][14][15][16] were deemed eligible for the current systematic review. The included trials encompassed a total of 378 extracted human teeth.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of seven in vitro studies 3,[11][12][13][14][15][16] were deemed eligible for the current systematic review. The included trials encompassed a total of 378 extracted human teeth.…”
Section: Resultsmentioning
confidence: 99%
“…However, at the 1-week and 1-month intervals, Coltosol exhibited superior sealing performance compared to Compoglass. Hajaj et al 12 compared the characteristic sealing in singlerooted and multirooted teeth and found that GIC exhibited superior sealing performance in single-rooted teeth compared to Coltosol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations